Libras and Chemistry: a look at education and teaching journals (Research, Society and Development, 2023)
This work aims to identify the thematic focuses between the relationship between the Brazilian Sign Language - Libras and the Teaching of Chemistry in Education and Teaching journals. The work is a state-of-the-art bibliographical work that had as source and discussion scientific articles published in periodicals in the area of Education and Teaching belonging to the Coordination for the Improvement of Higher Education Personnel (CAPES) portal, over a period of 10 years. The mapping was carried out in journals evaluated in Qualis A1, A2, A3 and A4 in the (Quadriennium 2017-2020). The analysis of the articles was through Discursive Textual Analysis. The data indicate that the works found deal with the themes of didactic studies, empirical studies, revision and construction and use of inclusive didactic materials.